Bone Resorption in Apical Periodontitis Enhanced by Cigarette Smoke Inhalation: Histometric, Immunohistochemical, and Microtomographic Analysis in Rats - Veiga Vasques, Ana Maria [UNESP]; da Silva, Ana Claudia Rodrigues [UNESP]; Bueno, Carlos Roberto Emerenciano [UNESP]; Duarte, Marco Antonio Hungaro; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP] (Elsevier, 2024)
Introduction: This study evaluated the effects of cigarette smoke inhalation (CSI) on apical periodontitis (AP) induced in rats by histometric, immunohistochemical, and microtomographic analysis. Methods: A total of 32 male Wistar rats were divided into 4 experimental groups (n = 8): control, CSI, AP, and CSI + AP. Rats in the CSI and CSI + AP groups inhaled cigarette smoke by remaining inside a smoking chamber for 8 minutes 3 times a day for 50 days. After 20 days of smoke inhalation, rats in the AP and CSI + AP groups had the pulp of their first right lower molar exposed to induce AP. Blood was collected on day 50 to evaluate nicotine and serum cotinine levels. The animals’ mandibles were removed for histologic processing to evaluate bone resorption by histometric, immunohistochemical (receptor activator of nuclear factor kappa B ligand/osteoprotegerin), and microtomographic analysis. The Student t test was applied. Results: Histometric analysis showed a larger area of bone resorption (P < .05) and microtomographic analysis found greater resorption volume (P < .001) for the CSI + AP group compared with the AP group. The CSI + AP group presented a high RANKL immunostaining pattern compared with the AP group (P < .001). Conclusions: CSI increased bone resorption caused by AP.
Keywords: Apical periodontitis; bone resorption; endodontics; oral infection; smokers